Costs of broad-based stock option plans - Oyer, Paul; Schaefer, Scott (Journal of Financial Intermediation, 2006)
We generate estimates of the costs of broad-based stock option programs under varying assumptions about why firms use these pay schemes. We show that, if accounting considerations alone drive option grants, a typical firm in our sample incurs between 50 cents and one dollar of real costs in order to increase reported pre-tax net income by one dollar. This cost is reduced, but is still quite substantial, if accounting leads firms to grant options rather than restricted stock. We also show that, if option grants are efficient, the patterns in our data are consistent with firms using these grants to attract and retain employees.